Preparation of High Stability Pd/Ceramic/Ti-Al Alloy Composite Membranes by Electroless Plating - Zhang, Dongqiang; Zhao, Jing; Yang, Ping; Chen, Yanan; Fan, Yiqun (Frontiers in Chemistry, 2020)
The high stability Pd/ceramic/Ti-Al alloy composite membranes were prepared by electroless plating. Ceramic membranes prepared by in-situ oxidation method were applied as an inter-diffusion barrier between the Pd layer and the Ti-Al alloy support to prevent intermetallic diffusion. The stability of ceramic membranes in H2 atmosphere was studied at high temperatures. The permeation performance and stability of Pd/ceramic/Ti-Al alloy composite membranes were also investigated. The results shown that the thickness, pore size and microstructure of ceramic membranes shown no observable change after treatment in H2 atmosphere at high temperatures, which indicated that the ceramic membranes prepared by in-situ oxidation method were stable in H2 atmosphere at high temperatures. The thickness of the Pd membrane was approximately 13 µm. The hydrogen permeability and H2/N2 selectivity through the Pd composite membrane was 2.13×10-3 mol m-2 s-1 Pa-0.5 and 600 at 500 °C, respectively. In addition, the H2 flux, N2 flux and H2/N2 selectivity remain relatively constant at same condition in three heat cycles, which indicated that the structure of the Pd composite membranes was stable.